45.151224 Peningkatan Kesadaran Orang Tua dan Anak di Sukorahayu Terkait Dampak Globalisasi Teknologi - Septyani Delvytri Kuranta; Tiarma Galatia Sihotang; Maria Prima Novita; Natalie Desta Karunia; Cendri Prima Crist Wijayanti; Gilbert Josafat Fanggidae (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2025)
The development of technology in the era of globalization creates a significant transformation in people's lives. Gadgets, as one of the most frequently used technologies, have both positive and negative impacts. Children are a generation that is vulnerable to gadget addiction. Early gadget addiction in children can potentially disrupt their development and hinder their ability to interact with their environment. In this case, parents and children to understand the impacts of gadget usage and adopt wise attitudes and behaviors. Therefore, students of the Institutional Practice Course at Satya Wacana Christian University organized a community service activity to the impact of excessive gadget use, with the aim of increasing the awareness of parents and children. Focus of this activity is on the community in Sukorahayu-Ampel Boyolali Village, both parents and children. This is driven by the problems in Sukorahayu Village, where the majority of children are starting to experience gadget addiction.